AN ANALYSIS OF THE APPLICABLE LAWS ON THE PROTECTION OF TRADITIONAL KNOWLEDGE AND CULTURAL EXPRESSIONS IN NAMIBIA (The Pretoria Student Law Review, 2021)
Traditional knowledge (TK) and cultural expressions are morevulnerable to infringements because of their nature and the lack of protection as intellectual property (IP) under many legal systems. TK can, however, contribute to the social and economic development of a country, the preservation of cultural heritage, and the increase in innovation and invention. It is for this reason that it is important to enact laws and formulate policies that recognise, promote, and protect TK and cultural expressions. An analysis was made on the protection offered under Namibian laws to holders of TK and cultural expressions and considered the adequacy and effectiveness of such laws. The findings show that on a regional level, Namibia is a party to the Swakopmund Protocol on the Protection of Traditional Knowledge and Expressions of Folklore, however, the Protocol has not been incorporated into national IP-related laws. In terms of domestic laws, there are no IP laws that expressly recognise and protect works of TK and cultural expression. However, there are policies such as the National Intellectual Property Policy 2019-2024 and the Namibia Arts, Culture and Heritage Policy 2021/2022-2023/2026, which recognises the value of TK and the need to protect TK and cultural expressions. Therefore, it is recommended that government should develop a sui generis system that can help foster the preservation and development of TK and cultural expressions. The system should take into consideration the current social and economic structures so that it can be effective. The Swakopmund Protocol on the Protection of Traditional Knowledge and Expressions of Folklore can be used as a guide in developing a sui generis system for Namibia.
Keywords: traditional knowledge; intellectual property; Namibian folklore; cultural expression; socio-economic development